2022
DOI: 10.3390/foods11020195
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Lactobacillus plantarum ZZUA493 and Its Application to Extend the Shelf Life of Chinese Steamed Buns

Abstract: Lactic acid bacteria (LAB) can produce many kinds of antifungal substances, which have been widely proven to have antifungal activity. In this study, 359 strains of LAB were screened for antifungal activity against Aspergillus niger (A. niger) using the 96-well microtiter plate method, and three showed strong activity. Of these, ZZUA493 showed a broad-spectrum antifungal ability against A. niger, Aspergillus oryzae, Trichoderma longibrachiatum, Aspergillus flavus and Fusarium graminearum. ZZUA493 was identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…plantarum LPP703 cultures were collected by centrifugation at different culture times, and then the supernatants were further filtered through a 0.2 µm membrane filter. The antifungal effect of the obtained cell-free supernatant (CFS) was assayed by microplate inhibition analysis [7]. Briefly, a 100 µL aliquot of Lpb.…”
Section: Determination Of Antifungal Activity Of Lpb Plantarum Lpp703...mentioning
confidence: 99%
See 1 more Smart Citation
“…plantarum LPP703 cultures were collected by centrifugation at different culture times, and then the supernatants were further filtered through a 0.2 µm membrane filter. The antifungal effect of the obtained cell-free supernatant (CFS) was assayed by microplate inhibition analysis [7]. Briefly, a 100 µL aliquot of Lpb.…”
Section: Determination Of Antifungal Activity Of Lpb Plantarum Lpp703...mentioning
confidence: 99%
“…The lactic acid bacteria (LAB) have received particular attention due to their generally recognized as safe status. It has been reported that LAB have potent antifungal activity against many fungal genera [5][6][7]. Various bioactive metabolites (such as proteinaceous substances, cyclic dipeptides, organic acids, fatty acids, and hydrogen peroxide) generated by LAB are closely associated with the inhibitory effect of LAB on fungi [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported a broad spectrum of antifungal activity by many Lactobacillus spp. due to various organic acids production [ 204 , 205 ]. According to Lavermicocca et al [ 206 ], PLA and OH-PLA synthesized by Lp.…”
Section: Lab Against Mycotoxins and Their Producersmentioning
confidence: 99%
“…The peptidoglycan layer has also been implicated. However, the binding capacity is highly variable: species- and strain-specific, greatly affected by pH and temperature, and mostly reversible [ 204 , 208 ]. Other mechanisms, such as the degradation of mycotoxins or their conversion to less toxic metabolites, are still waiting for proper experimental support [ 201 ].…”
Section: Lab Against Mycotoxins and Their Producersmentioning
confidence: 99%
“…LAB, like many probiotics, are generally recognized as safe (GRAS) [ 17 ]. During fermentation, LAB produce acidic substances that reduce the pH value of the environment and cause intracellular acid stress, resulting in unfavorable conditions for the growth of fungi in food products [ 18 ]. These acidic substances, such as lactic acid (LA), acetic acid (AA), propionic acid, formic acid, phenyllactic acid, and fatty acids, have shown antifungal properties [ 13 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%